Inheritance [videorecording (DVD)] : [a Nazi legacy and the journey to change it] - Moll, James (Docurama : Distributed by New Video, 2008)
Monika Hertwig never knew her father, Amon Goeth, commandant of the Plaszow Concentration Camp, and struggles with the legacy he left her. Sixty years later, she meets Helen Jonas, who served as Goeth's maid and prey.